Changes in Form and Style in Randai Performance at The Minangkabau Diaspora in Malaysia - Indrayuda, Indrayuda; Samsuddin, Mohd Effindi (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This article reveals the changes in form and style of the Randai performance performed by the Minangkabau’s diaspora in Malaysia. The novelty of this research is the study of changes in forms and styles in Randai carried out by the Malaysian Minangkabau diaspora. The disconnection of socio-cultural communication and the long distance between Minangkabau and Peninsular Malaysia impacts the shift in forms and styles of Randai in the Minangkabau diaspora. This research was conducted qualitatively by designing research works such as pre-field studies, by collecting preliminary data based on a diffusion approach. In the field stage, the informants were selected by snowball sampling. The interview and observation instruments were designed based on the performance structure and performance procedures. Researchers conducted data analysis using the techniques recommended by Spradley, namely: (1) domain analysis, (2) taxonomic analysis, (3) componential analysis, and (4) discovering cultural themes. The study results revealed that the forms and styles were caused by mixing cultures between the diaspora and the Malaysian Malays. These changes were done so that the local community could accept Randai. In addition, Randai can be easily learned and cultivated by the Malay Malays and easily expressed by the Malaysian community and the Minangkabau diaspora as the perpetrators of Randai. These changes occur through a process of adaptation and acculturation. The implication of this research is the emergence of a new Randai model, namely Randai, which refers to local culture, both from the aspect of the story, Silat style, and music, as an identity and tradition for the Malaysian Minangkabau diaspora for the future.